(3fTQ GddGdis - (3CHhGdMSf Ydj Hf CHj WGdH Hf YHO GdeWdH,J (B40 (3g` s
(3ChdgG (B:s
(3GdCda EjeGf GdeQA jYQa HEjeGfg CNhc COH GdeQA NjQ ef PgHg s
(3BNQgG (B:s
(3jShO GdeQA bheg HGdGMSGf Edjge HCS GdbdH QGMI GdfaS jSYO GdQLd HeUGMHI GdSYjO JeJ GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GfXQg eY GdeNWhW Qbe (B292 (3ef faS GdHYKIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdCOHs